Effect of a weak fiber interface coating in ZrB2 reinforced with long SiC fibers. (25th December 2015) - Silvestroni, Laura; Sciti, Diletta; Hilmas, Greg E.; Fahrenholtz, William G.; Watts, Jeremy
Abstract: This study reports the microstructural analysis and mechanical properties of a ZrB2 ceramic containing long BN-coated Hi-Nicalon SiC fibers. A composite was produced and thoroughly characterized by transmission electron microscopy to study the interfaces at the nanoscale level. Full densification was accomplished by hot pressing at 1450 °C. The fiber in the sintered material retained its pristine aspect, confirming that the coating was effective in preventing degradation due to interactions with the matrix. Pull-out was observed on fractured surfaces, but toughness values were about 4.5 MPa√m, which was comparable to those of ZrB2 materials with SiC additions in the form of particles or short fibers. However, the composites exhibited a controlled fracture behavior, as confirmed by a notably higher work of fracture, 140 J/m 2, compared with 20–30 J/m 2 of unreinforced ZrB2 or ZrB2 containing chopped fibers. Graphical abstract: Highlights: Production of a ZrB2 ceramic containing continuous BN-coated SiC fibers. TEM analysis revealed features at the nanoscale level inside fiber, fiber coating and at the coating/matrix interface. The BN-coating for Hi-Nicalon fiber effectively hindered fiber degradation during processing. The composite resulted more damage tolerant than monolithic ZrB2 or ZrB2 reinforced by discontinuous elements. The total and inelastic WOF values were notably higher than those measured for the short fiber composites.